The Role of Stakeholders in The Perhutani Puncak Area Bogor District, West Java - Pujiastuti, Sri; Amir, Firlie Lanovia (E-Journal of Tourism; Volume 11 Number 1 (March 2024)DO - 10.24922/eot.v11i1.113420, 2024)
Part of the North Tugu tourist village consists of forests, mountains, bays, waterfalls and plantations which are in conservation areas. The village has various problems related to tourism management. Some of the obstacles experienced by the organizers were the existence of several policies that conflicted both practically and constitutionally. This research aims to map tourist interest regarding management involving several stakeholders, such as Perhutani, Forest Village Community Institutions, Tugu Utara Tourism Village, Village-Owned Enterprises, PT Sumber Sari Bumi Pakuan (SSBP). The method used was descriptive qualitative, by conducting interviews with 7 (seven) informants, observation and document study. The analysis tool used is NVivo R1-7. The results of the analysis show that the management of the North Tugu Tourism Village is at the involvement stage towards the development stage. This research resulted in the identification of the roles of stakeholders, based on management collaboration, it appears that Forestry and Tourism Villages play a significant role as managers who are directly involved technically. The stakeholder collaboration aims to preserve the natural sustainability of the North Tugu Tourism Village and improve the welfare of the community in the forest area.